Improving Learning Outcomes in Islamic Religious Education and Ethics Through the Teams Games Tournament Learning Model in Grade XI of SMA Negeri 1 Nguntoronadi - Rhisma Ihwanul Khoriyah; Ratih; Ali Mahbub (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research is motivated by the low learning outcomes of students in the subject of Islamic Religious Education and Ethics in grade XI 1 SMA Negeri 1 Nguntoronadi. Based on the results of initial observations, the level of student learning completeness is still low because the learning process tends to be teacher-centered so that students are less active and less motivated in participating in learning. This research aims to improve student learning outcomes through the application of the Teams Games Tournament (TGT) learning model. This research is a class action research which is carried out in two cycles. Each cycle includes the stages of planning, implementation of actions, observation, and reflection. The research subjects amounted to 33 students in class XI 1 of SMA Negeri 1 Nguntoronadi. Data collection techniques are carried out through observation, learning outcome tests, and documentation. Data were analyzed using quantitative and qualitative descriptive analysis techniques. The results of the study show that the application of the Teams Games Tournament learning model is able to improve student learning outcomes. In the pre-cycle stage, the percentage of student learning completeness only reached 10%. After the TGT learning model was applied in the first cycle, learning completeness increased to 63%. Furthermore, in cycle II it increased to 100%. Student activities also increased from 78% in cycle I to 90% in cycle II. Teacher activity increased from 76% to 90%. This improvement shows that the TGT learning model is able to create an active, fun learning atmosphere, and encourage student involvement in the learning process. Based on the results of the study, it can be concluded that the application of the Teams Games Tournament learning model has proven to be effective in improving the learning outcomes of students in the subject of Islamic Religious Education and Ethics in grade XI 1 SMA Negeri 1 Nguntoronadi.